PEMANFAATAN LIMBAH PADAT INDUSTRI PANGAN SEBAGAI BAHAN BAKU PAKAN TERNAK AYAM BROILER - Mohammad Mirwan; Rausan Fikri Arman (EnviroUS, 2022)
Porang tubers (Amorphophallus muelleri) belonging to the family Araceae. Sludge produced by by-products produced in the production process will greatly affect the receiving environment, especially food waste with high organic content. In poultry farming, 70% of the total cost of production is used to provide animal feed. There-fore, this study aims to utilize sludge from PT AMBICO as broiler animal feed in-gredients. The method used in this research is by fermentation and adding ingredi-ents to improve the nutritional quality of the animal feed. Data analysis using prox-imate analysis, calcium, and phosphorus, then the results are compared with the quality requirements of SNI 8173.3-2015. Where the most optimum mixing ratio overall the results of this feed are still many that do not meet SNI so that it cannot be said to be feasible as a good broiler chicken feed. However, the results of the K4 variable test still have 2 parameters that meet the SNI quality standard, namely the Water Content which results in 13.08% and Calcium which results is 0.96%